Pendekatan Holistik pada Penyuluhan Remaja di 17 SMA Sederajat di Kabupaten Rokan Hilir Provinsi Riau - Mirnawati; Widia Sari Rusma; Dian Noviana; Meli Saputri; Siti Kholijah; Delima Sari; Rahmi Nurrizky; Anggy Saputri; Dini Safira; Fittria Ayu Sahputri; Rambe, Wahyudi; Afriani, Indri; Qisthi, Mashallia; Al Khofifah, Salsabila; Eginanda Putri, Airani; Hardiansyah, Rian; Zahara, Siti; Adzmi Yulistina, Amaliatul (Jurusan Ilmu Sosial dan Ilmu Politik, 2024)
This counseling paradigm, implemented within the Abdurrab University Community Service Program (KKN) in 17 secondary schools across Rokan Hilir Regency, Riau Province, espouses a holistic approach to adolescent development, encompassing the physical, cognitive, social, and environmental dimensions of well-being. The program's core focus, encompassing reproductive health, traditional family medicine utilization (TOGA), personal image enhancement, bullying prevention, and promotion of a clean and healthy lifestyle (PHBS), addresses key challenges faced by adolescents arising from health and self-development knowledge gaps. This study aims to evaluate the impact of the counseling interventions, delivered through participatory and direct consultations, upon student understanding and behavior. The results showed that significant increase in student awareness and knowledge regarding the targeted topics, concurrent with a notable shift towards positive behavioral changes.